2010
DOI: 10.4067/s0718-58392010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrate and Labile Carbon on Denitrification of Southern Temperate Forest Soils

Abstract: The pressure for anthropogenic land use changes and logging of temperate forests in southern Chile is rapidly increasing, with its potentially high impacts on the capacity of soils to retain important limiting elements. We tested the hypotheses that logging increases the denitrification rates and nitrate and C limitation of denitrifiers activity would be higher in soils of unlogged, old-growth forests than in soils of logged forests. Potential denitrification rates were estimated by the acetylene inhibition as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…A higher capacity for N removal from the Melaleucas might be expected given the more saturated, organic-rich soils found in these systems, which are favourable for denitrifier activity (Cardenas et al, 2017;Tomasek et al, 2019). The mangrove soils, however, have higher nitrate availability, more labile carbon and lower C:N, which all maintain high rates of denitrification (Klemedtsson et al, 2005;Luo et al, 1999;Pérez et al, 2010). The large variation in soil moisture content between the mangrove and Melaleuca soils used in the incubation experiments likely had a large effect on biogeochemical processing, however, the soil moisture was reflective of the expected higher saturation in Melaleuca soils in natural systems.…”
Section: Controls and Mechanisms Of Carbon And N Cyclingmentioning
confidence: 99%
“…A higher capacity for N removal from the Melaleucas might be expected given the more saturated, organic-rich soils found in these systems, which are favourable for denitrifier activity (Cardenas et al, 2017;Tomasek et al, 2019). The mangrove soils, however, have higher nitrate availability, more labile carbon and lower C:N, which all maintain high rates of denitrification (Klemedtsson et al, 2005;Luo et al, 1999;Pérez et al, 2010). The large variation in soil moisture content between the mangrove and Melaleuca soils used in the incubation experiments likely had a large effect on biogeochemical processing, however, the soil moisture was reflective of the expected higher saturation in Melaleuca soils in natural systems.…”
Section: Controls and Mechanisms Of Carbon And N Cyclingmentioning
confidence: 99%
“…higher N 2 O emissions at lower C/N), similar to the observations of Huang et al ( 2004 ) and Chen et al ( 2013 ). The highest emissions were consistently observed from the HC amended soils at all WFPS, with high levels of readily available (mineral) N and labile C to promote denitrification at the highest WFPS (Robertson and Tiedje 1988 ; Regina et al 1998 ; Mohn et al 2000 ; Garcia-Montiel et al 2003 ; Bateman and Baggs 2005 ; Wallenstein et al 2006 ; Pérez et al 2010 ). The significant increase in N 2 O emissions we observed once WFPS exceeded 75% has been demonstrated in many studies (Weier et al 1993 ; Rudaz et al 1999 ; Ruser et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, N 2 O emissions can be stimulated by the application of N fertiliser and organic soil amendments (Aulakh et al 1984 ; Eichner 1990 ; Wang et al 2011 , 2012 ). Decomposition of organic materials generates labile C compounds (Chatterjee et al 2008 ) which enhances the denitrification rate in soils (Robertson and Tiedje 1988 ; Wallenstein et al 2006 ; Pérez et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen addition can increase (Brenner et al, 2005;Lu et al, 2011;Corre et al, 2014), decrease (Lovett et al, 2013;Cai et al, 2014), or have no effect (Brenner et al, 2005;Wang et al, 2014) on net nitrification. Similarly, denitrification was found to increase (Perez et al, 2010), decrease (Bengtsson and Bergwall, 2000;Berntson and Aber, 2000), or remain unchanged (Wallenstein et al, 2006) under N addition. A meta-analysis indicated that N addition significantly increased net N mineralization, nitrification, and denitrification by 25, 154, and 84%, respectively, but did not change N immobilization (Lu et al, 2011).…”
mentioning
confidence: 91%